Analysis of Development Strategy Based on Dynamic Capabilities in UMKM Kulea Coffee in Bandar Lampung - Nadia Garlyna; Alfira Putri; Amanda Sharfina; Kaila Febiola; Sintia Nurul (Journal of Innovation, Business Management and Entrepreneurship, 2025)
This study analyzes the development strategy of UMKM Kulea Coffee in Bandar Lampung based on the perspective of dynamic capabilities. UMKM operate in a highly dynamic business environment characterized by changing consumer preferences, fluctuating demand, and increasing competition, which requires adaptive and flexible strategies. The objective of this research is to examine how UMKM Kulea Coffee applies dynamic capabilities in developing its business strategy. This study uses a qualitative descriptive approach with a case study method. Data were collected through semi-structured interviews with the business owner and internal parties, supported by observation and documentation. The analysis is based on three dimensions of dynamic capabilities, namely sensing, seizing, and reconfiguring. The results show that Kulea Coffee demonstrates sensing capability through its ability to identify changes in consumer preferences and seasonal demand fluctuations. Seizing capability is reflected in strategic decisions such as fulfilling custom requests, implementing a booking system, and adjusting menu variations during certain periods. Meanwhile, reconfiguring capability is seen in internal adjustments, particularly in improving service quality and work processes to enhance customer satisfaction. Overall, the findings indicate that the application of dynamic capabilities enables UMKM Kulea Coffee to adapt to environmental changes and supports business sustainability and competitiveness in the local market.